2001
DOI: 10.1074/jbc.m106651200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Characterization of Two Medium-chain Acyl-CoA Synthetases, MACS1 and the Sa Gene Product

Abstract: In this study, we identified and characterized two murine cDNAs encoding medium-chain acyl-CoA synthetase (MACS). One, designated MACS1, is a novel protein and the other the product of the Sa gene (Sa protein), which is preferentially expressed in spontaneously hypertensive rats. Based on the murine MACS1 sequence, we also identified the location and organization of the human MACS1 gene, showing that the human MACS1 and Sa genes are located in the opposite transcriptional direction within a 150-kilobase region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 27 publications
5
54
0
Order By: Relevance
“…synthesis has been ascribed to a mitochondrial medium-chain acyl-CoA synthetase known as ACSM1 (34,35). This is an enzyme of broad acyl chain specificity, including several xenobiotics that contains each of the motifs of this well studied enzyme family (39,40). However, ACSM1 has been reported to convert both the natural (R)-and unnatural (S)-lipoate isomers to their adenylates and also uses GTP to produce lipoylguanylate, which is released from the enzyme to serve as a lipoyl transferase substrate (14).…”
Section: Discussionmentioning
confidence: 99%
“…synthesis has been ascribed to a mitochondrial medium-chain acyl-CoA synthetase known as ACSM1 (34,35). This is an enzyme of broad acyl chain specificity, including several xenobiotics that contains each of the motifs of this well studied enzyme family (39,40). However, ACSM1 has been reported to convert both the natural (R)-and unnatural (S)-lipoate isomers to their adenylates and also uses GTP to produce lipoylguanylate, which is released from the enzyme to serve as a lipoyl transferase substrate (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, this premise is not true for medium-chain fatty acids; these fatty acids can be activated inside the mitochondrial matrix and do not rely on carnitine palmitoyltransferase 1 for mitochondrial uptake (Tol, 1975;Rasmussen et al 2002). Thus, even when neutral mediumchain fatty acids reach the mitochondrial matrix they can be activated to fatty acyl-CoA and directed to b-oxidation (Fujino et al 2001). Obviously, these fatty acids do not need to (and should not) be exported from the matrix, eliminating a role for UCP3 in the handling of these specific medium-chain fatty acids.…”
Section: Mitochondrial Uncoupling Protein-3 To Prevent Lipid-induced mentioning
confidence: 99%
“…Both rat and mouse homologues showed kidney and liver specific gene expression. 41 Three sequence variants, silent transitions c45T-C and c720G-A and c314insT were detected in Ks-2 gene. All of these variants were homozygous in both patients and controls.…”
Section: Haplotype Analysismentioning
confidence: 99%
“…A recent study identified the protein as a medium-chain acyl-CoA synthetase. 41 Six sequence variants were detected in the Ks-1 gene. Two transitions, c340G-A and c428T-C, changing 114Gln-Lys and 143Leu-Ser, respectively, transversion g1166C-A, and a homozygous single base pair deletion g3385delT were found in both patients and controls.…”
Section: Haplotype Analysismentioning
confidence: 99%